Forecasting impacts of climate change on changes of municipal wastewater production in wastewater reuse projects. (20th December 2021) - Shakeri, Hossein; Motiee, Homayoun; McBean, Edward
Abstract: Treated municipal wastewater is reused for agriculture, industry and urban needs. Municipal wastewater production rates can change based on climate variables. Since greenhouse gas emissions intensify climate change, changes in wastewater production under climate change may disrupt wastewater reuse plans. Despite these issues, no approach has been proposed to forecast changes in municipal wastewater production under future climate change based on emissions scenarios. No model has been developed to quantitatively assess the net relationship between climate variables and human behaviors in municipal wastewater production. Given these gaps, this research develops an approach for forecasting the impacts of climate change on future changes of municipal wastewater production in wastewater reuse projects of large cities. Wastewater production volumes under future emissions scenarios are forecast by developing Multi-Layer Perceptron network and Fuzzy model. Fuzzy C-Means clustering and Mamdani system increase the flexibility of forecast model under nonlinear conditions, providing a novel optimal structure. Increasing the number of synoptic stations and climate variables, and employing weighted-mean of eight climate models, uncertainties in projecting magnitudes of climate change are reduced. As a case study, forecasting Tehran's municipal wastewater production under scenarios of Representative Concentration Pathway showed that daily mean temperature increases by 1.29 °C and subsequently, daily wastewater production increases on average by 36.9% for future two decades. This approach showed 11%–22% of untreated excess wastewater beyond capacity of wastewater reuse system for 2031–2040. For this case, previous studies based only on historical trends have predicted untreated excess wastewater quantities to be zero which does not match even the current measurements. Futuristic insights of this research provide more realistic forecasts to both facilitate and maintain reuse plans of treated municipal wastewater as a cleaner production under future climate changes. Graphical abstract: Image 1 Highlights: Link between climate changes and human behaviors in wastewater production is modeled. Mamdani system and C-Means clustering improve forecasting nonlinear wastewater rates. Flow rates forecast under emission scenarios show realistic impact of climate change. The proposed method reveals 11% of unforeseen capacity for Tehran wastewater system. Net share of climate change in increasing wastewater production is forecast at 33%.